RETRACTED: A 1 year course of starch- and sucrose-reduced diet used by irritable bowel syndrome patients with diarrhoea and the effect of genetic variants - Garcia-Etxebarria, Koldo; Gayoso, Lucía; Arzallus, Teresa; Montalvo, Isabel; Lizasoain, Jacobo; Izagirre, Arantzazu; Ezkurra, Ander; D’Amato, Mauro; Etxeberria, Usune; Bujanda, Luis (Frontiers in Nutrition, 2023)
Background: Irritable bowel syndrome is a heterogeneous syndrome and it is difficult to find an effective treatment. Previously, a starch-and sucrose-reduced diet (SSRD) demonstrated promising short-term outcomes. It was proposed that genetic variants in the sucrose-isomaltase gene might influence this success. Our aim in this work was to extend the follow-up study to 1-year and to analyse the effect of the genetic variants of genes involved in starch and sucrose metabolism.Methods: IBS-SSS questionnaire, IBS-QoL questionnaire and questionaires about adherence, difficulty and food assessment were sent to 34 patients after 6 months and 1-year after the end of the dietary intervention. In addition, 11 genes involved in sucrose and starch metabolism were sequenced.Results: 23 participants responded to the 6-month follow-up and 16 to the 1-year follow-up. IBS-SSS total value increased 59.71% in the 6-month follow-up compared with the end of the intervention (P=0.0018), and 55.39% in the 1-year follow-up (P=0.0166); while IBS-QoL score decreased 24.09% (P=0.0002) and 18.07% (P=0.0022), respectively. The adherence decreased by 29.11% (P=4.8x10 -5 ) and 27.21% (P=0.0054), respectively. In addition, carriers of pathogenic variants on the SI gene showed a slightly better performance than non-carriers. Finally, the participants showed less satisfaction over time with 18 allowed foods in the diet.Conclusions: Over time the SSRD is difficult to follow and the genotype might affect the performance of the diet. Since this diet could be a promising therapeutic option, a larger cohort needs to be analysed to validate the results and to compare it with other diets.